Building Indonesian Democracy: Maintaining The Balance Between Civility, Reconciliation, and The Role Of Opposition In Monitoring Power - Ida Ayu Gerhana Saraswati Dharmmesta; Bambang Satriya; Supriyadi (Innovation Business Management and Accounting Journal, 2025)
This research aims to discuss the function of the opposition in the context of democracy and the important role of the opposition in monitoring power. The research method used is a qualitative approach with descriptive analysis. The research findings show that Indonesian democracy requires a harmonious balance between maintaining social harmony through civility and reconciliation and ensuring the role of an effective opposition as a watchdog of power. The opposition is vital in maintaining transparency and accountability and encouraging government policies that are more responsive to public interests. Without constructive opposition, democracy risks losing its essence as an open and accountable system. This research contribution highlights the importance of the opposition as a partner to the government in creating inclusive and effective policies. It also emphasizes the need for regulations that strengthen the opposition's position in parliament and build a competitive yet polite political culture. Research recommendations include strengthening opposition rights, reducing fat coalitions, and increasing freedom of speech and media to strengthen a more mature and sustainable Indonesian democracy.